Competition and utility regulation - Tassano Velaochaga, Hebert Eduardo (2016)
With the entry into force of the Constitution of Peru of 1993, the economic model of social market economy, which was accompanied by an institutional reform, creating four (4) regulators of utilities and one (1) competition agency, was established. The economic model of social market economy, guarantees free competition in the market as a general rule, establishing a regulatory framework for public services that before the reform, were managed directly by the State. Thus, in this paper we will learn how to set up the Peruvian institutional framework and what are the main similarities and differences between competition and regulation, for which we will detail the functions of the competition agency and regulatory bodies as well as interaction between the two.